Sosialisasi Pentingnya Promosi Sekolah Guna Meningkatkan Jumlah Siswa di Era Pandemi Covid-19 - Pamungkas, Iing; Irawan, Heri Tri; Prasanti, Nissa; Sofiyanurriyanti, Sofiyanurriyanti; Hadi, Khairul; Adib, Adib; Akmal, Abdiel Khaleil; Irawan, Risnadi; Kasmawati, Kasmawati (Universitas Teuku Umar, 2022)
Community service activities are a medium for delivering science and technology to the community. This community service is carried out by a lecturer in the Department of Industrial Engineering, Faculty of Engineering, Teuku Umar University. The theme of this community service is the importance of promoting schools in order to increase the number of students during the COVID-19 pandemic. The purpose of this community service is to provide an overview to the foundation about the importance of introducing the profile of the foundation to the surrounding community, and as an effort to increase the number of new students at the Makmue Raya Foundation. Participants in this community service are foundation administrators, teachers and students of Madrasah Aliyah (MA) and Madrasah Tsanawiyah (MTs) under the auspices of the Makmue Raya foundation, totaling 83 people. Community service participants participated in the socialization in the form of lectures, discussions and questions and answers about the importance of school promotion during the COVID-19 pandemic. The output of this community service is as basic knowledge about school promotion to foundations, and can introduce school promotion methods during the covid-19 pandemic to foundations.